Pengaruh CSR dan GCG terhadap Kinerja Keuangan Perusahaan dengan Manajemen Laba sebagai Variabel Mediasi - Sihotang, Diva Amelia; Tantina Haryati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to examine the effect of Corporate Social Responsibility and Good Corporate Governance on the financial performance of technology sector companies listed on the IDX with earnings management as a mediating variable in the 2019-2022 period. The type of research used is a quantitative approach. The number of samples in this study were 13 companies with 4 years of observation period selected using purposive sampling method. The analysis and hypothesis testing used is PLS-SEM using SmartPLS software. The results showed that CSR and GCG variables were able to influence financial performance and earnings management. Earnings management variables cannot affect the company's financial performance. Earnings management cannotmediate the relationship between CSR and GCG on financial performance. The conclusion of this study is that bothCSR and GCG play an important role in improving the company's financial performance. Companies committed tosocial responsibility and good governance mechanisms tend to be financially healthier. On the other hand,earnings management practices are often practiced but do not have a significant impact on financial performance.